2020
DOI: 10.3390/nano10040753
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and Thermal and Self-Healing Properties of Graphene-Thermopolyurethane Flexible Conductive Films

Abstract: We fabricated graphene-thermopolyurethane (G-TPU) flexible conductive film by a blending method and systematically investigated the electrical, thermal and self-healing properties of the G-TPU flexible conductive film by infrared light and electricity. The experimental results demonstrate that the G-TPU composite films have good conductivity and thermal conductivity in the appropriate mass content of graphene in the composite film. The composite films have the good electro-thermal and infrared light thermal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 36 publications
0
22
2
Order By: Relevance
“…Chen et al reported that they prepared stretchable and conductive G-TPU nanocomposite foam materials via water vapor induced phase separation technology [ 18 ]. Strankowski et al reported that they used graphene nanoplates and reduced graphene oxide as fillers to prepare two kind of thermally reinforced and mechanically reinforced TPU composites [ 25 ]. Cataldi et al reported that they prepared self-healing flexible conductive cotton textiles by impregnating cotton fabrics in graphene and thermoplastic polyurethane-based dispersions [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al reported that they prepared stretchable and conductive G-TPU nanocomposite foam materials via water vapor induced phase separation technology [ 18 ]. Strankowski et al reported that they used graphene nanoplates and reduced graphene oxide as fillers to prepare two kind of thermally reinforced and mechanically reinforced TPU composites [ 25 ]. Cataldi et al reported that they prepared self-healing flexible conductive cotton textiles by impregnating cotton fabrics in graphene and thermoplastic polyurethane-based dispersions [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The photothermal conversion temperature in this area is higher than the surroundings, so, "hot spots" are formed [39,41]. It should be pointed out that the near-infrared photothermal conversion efficiency of the GO-TPU film is slightly different from that of the graphene-TPU film we previously reported [44]. Comparing the experimental results of the two, it can be seen that the near-infrared photothermal conversion efficiency of graphene is higher than that of GO.…”
Section: Near-infrared Photothermal Response Of Go-tpu Flexible Filmsmentioning
confidence: 66%
“…In addition, with the increase of the infrared lamp irradiation time, the sample surface gradually brightened. This may be due to the thermal melting and solidification of the GO-TPU film [16,[42][43][44][45]. After the infrared lamp is turned on, as the irradiation time increases, the scratch is gradually repaired.…”
Section: Self-healing Of Go-tpu Filmsmentioning
confidence: 99%
See 2 more Smart Citations